2012
DOI: 10.1159/000342313
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Alcohol Choice among Russians: Evidence from a Quantitative Study

Abstract: Aims: Qualitative studies find that men and women in Russia have different preferences for alcoholic beverages, but quantitative evidence for gender differences in beverage type choice remains scarce. The purpose of this article is to test numerically whether and to what extent men and women in Russia differ in terms of preferences for type of drink, such as vodka, wine and beer. Methods: Results are based on multinomial logistic regression and ordinary least squares regression analyses of the Russian Longitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…That the associations between sexual risk and childhood abuse might be moderated by gender is consistent with evidence in the literature that sexual risk behavior [29,30], IPV [45], and drinking patterns and motivations [46,47] may vary by gender. For example, a study investigating the association between depression symptoms and alcohol use found that this relationship observed a non-linear U-shaped relationship among men and a linear trend among women [48].…”
Section: Discussionsupporting
confidence: 83%
“…That the associations between sexual risk and childhood abuse might be moderated by gender is consistent with evidence in the literature that sexual risk behavior [29,30], IPV [45], and drinking patterns and motivations [46,47] may vary by gender. For example, a study investigating the association between depression symptoms and alcohol use found that this relationship observed a non-linear U-shaped relationship among men and a linear trend among women [48].…”
Section: Discussionsupporting
confidence: 83%
“…Sex differences in excessive alcohol consumption thus seem to play a substantial role in explaining the LE gender gap. The evidence showing that alcohol consumption levels are higher and alcohol consumption patterns are risker among men than among women of young and working ages has generally been explained by differences in gender roles (6,9), as well as by differences in strategies for coping with stress (10,30).…”
Section: Discussionmentioning
confidence: 99%
“…Men have likely been affected by these developments more than women for the simple reason that men tend to drink more than women. However, in line with the general convergence in the lifestyle behaviours of men and women as a result of changes in the position of women in society (34), women in Russia and worldwide have recently started adopting the alcohol consumption behaviours of men (9,39,40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another notable finding is that while the frequency of drinking had a significant positive relationship with VI in a dose-response manner in men, the risk of VI in women was not associated with drinking frequency. According to previous literature, men tend to prefer strong alcoholic beverages such as vodka or liquor [40] and are more likely to be involved in heavy or binge drinking [41], whereas women typically prefer mild alcoholic beverages such as beer or wine and are likely to be mild drinkers. This tendency is also reflected in our data wherein 91% of those who consumed ≥40 g/day of alcohol were men.…”
Section: Discussionmentioning
confidence: 99%